From Stories about Living to Living the Stories: Composing a Collective Idea of Home in an Independent Living Project - Cuppari, Antonella (INSTED: Interdisciplinary Studies in Education & Society, 2022)
Being able to choose where to live and with whom is a right. However, the issue of self-determined living is complex and can't be taken for granted, especially in presence of disability conditions. It involves the micro level of individual stories, the meso level of family stories, professional actions and community relations, and the macro level of the culture of social inclusion within society. In this contribution, the author narrates a cooperative enquiry with social workers, volunteers and family members of people with intellectual disabilities involved in an independent living project in Northern Italy. Thinking by stories (Bateson, Bateson, 1987) constituted a biographical, poetic and imaginative way to activate a process of systemic reflexivity (Formenti, Rigamonti, 2020) starting from the relationships between the participants. This way of thinking together created conditions to question dominant discourses and to compose a new collective idea of home in independent living projects.